The Role of Criminalistic Science in Investigating A Hit-and-Run Crimes - Bawole, Herlyanty Y. A.; Bawole, Grace Y (Jurnal Daulat Hukum, 2024)
The purpose of this research is to investigate the role of criminalistics science in solving criminal cases, utilizing a literature review method (Library Research). The literature review method is employed, which involves analyzing relevant books, legislation, and other written materials related to the subject matter under discussion by the author. Forensic sciences such as Forensic Medicine, Forensic Physics, Ballistic and Metallurgic Forensics, Photography, and Photographie Forensic, Forensic Fingerprinting. These auxiliary criminalistics sciences play a crucial role in investigating hit-and-run crimes through the application of techniques and tactics in finding perpetrators.